2002
DOI: 10.3354/meps240157
|View full text |Cite
|
Sign up to set email alerts
|

Polychaete species diversity in the central Pacific abyss: local and regional patterns, and relationships with productivity

Abstract: We investigated the relationship between productivity and local species diversity, and the degree of species turnover, at 8 sites on the central equatorial Pacific abyssal plain. The 8 sites span a 4-fold difference in seafloor particulate organic carbon (POC) flux and, hence, community productivity. The sites are similar in water depth (4300 to 5100 m), degree of isolation from terrigenous influences, and hydrodynamic regime. Three sites lie under the influence of equatorial upwelling, and are subject to enha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
125
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 144 publications
(140 citation statements)
references
References 66 publications
15
125
0
Order By: Relevance
“….08 ---P = 0.37 P = 0.37 --BD R 2 adj = 0.40 BD 2 : 0.14 LR = 8.21 R 2 m = 0.18 0.09 P < 0.001 P < 0.001 P < 0.01 P < 0.01 had a positive impact on nematode taxon diversity, measured as H and EG (20), consistent with earlier work on polychaetes (Glover et al, 2002) and nematodes (Lambshead et al, 2002) from the abyssal central Pacific. It was shown that seafloor POC flux declines from the Northeast Atlantic to the eastern Mediterranean (not considering seamount station GB1200) and with water depth (Pape et al, 2013), and hence this environmental factor may partly explain the observed bathymetric decline in taxon diversity (see Sect.…”
Section: Environmental Drivers Of Nematode Diversitysupporting
confidence: 78%
See 1 more Smart Citation
“….08 ---P = 0.37 P = 0.37 --BD R 2 adj = 0.40 BD 2 : 0.14 LR = 8.21 R 2 m = 0.18 0.09 P < 0.001 P < 0.001 P < 0.01 P < 0.01 had a positive impact on nematode taxon diversity, measured as H and EG (20), consistent with earlier work on polychaetes (Glover et al, 2002) and nematodes (Lambshead et al, 2002) from the abyssal central Pacific. It was shown that seafloor POC flux declines from the Northeast Atlantic to the eastern Mediterranean (not considering seamount station GB1200) and with water depth (Pape et al, 2013), and hence this environmental factor may partly explain the observed bathymetric decline in taxon diversity (see Sect.…”
Section: Environmental Drivers Of Nematode Diversitysupporting
confidence: 78%
“…the particulate organic carbon (POC) flux) and/or sediment characteristics (Gray, 2002;Stuart et al, 2003). Deep-sea diversity has been documented to vary positively (Glover et al, 2002; Published by Copernicus Publications on behalf of the European Geosciences Union. Lambshead et al, 2000Lambshead et al, , 2002, negatively (Gooday et al, 2012) or unimodally (Leduc et al, 2012a;McClain et al, 2012;Tittensor et al, 2011) with productivity for different taxa and geographic regions.…”
Section: Introductionmentioning
confidence: 99%
“…The data revealed a relatively high taxonomic diversity within all faunal categories, with many species new to science. These findings have been confirmed in the more recent literature (Peterson et al, 1998;Glover et al, 2002;Wang et al, 2010;Janssen et al, 2015;Paterson et al, 2015). Key faunal groups within the CCZ are the cnidarians, echinoderms and sponges among the megafauna, and polychaete worms, nematode worms and protozoan foraminifera among the macrofauna and meiofauna; these taxa represent >50% of faunal abundance and species richness in abyssal sediments and display a broad range of ecological and life history types.…”
Section: The Structure Of Faunal Communities In the Cczsupporting
confidence: 80%
“…Porcupine, Madeira, Tagus, and Cape Verde Abyssal Plains; Equatorial Pacific: DOMES, ECHO1, and PRA sites) was the low relative abundance of Spionidae (Glover, 2000;Glover et al, 2001Glover et al, , 2002. When comparing Sta.…”
Section: Sta M Polychaete Assemblagementioning
confidence: 99%